Photoexcitation-induced carrier dynamics in an undoped InAs/GaSb quantum well. (10th March 2016) - Li, Junbin; Wu, Xiaoguang; Wang, Guowei; Xu, Yingqiang; Niu, Zhichuan; Zhang, Xinhui
Abstract: The carrier lifetime in an InAs/GaSb quantum well grown by molecular beam epitaxy has been investigated by the time-resolved pump–probe reflectivity (PPR) measurement. It is found that the PPR response shows a sign reversal when tuning excitation energy from 1.033 to 0.954 eV. A model is adopted, in which one takes into account the band gap renormalization and band filling effects, to simulate the temporal evolution of the PPR response. The carrier decay time is then extracted at different excitation energy. The carrier decay time of 98 ps obtained at a close resonant excitation of 0.827 eV is denoted as the carrier lifetime at room temperature. The temperature-dependent PPR is also examined to further investigate the dominant carrier decay mechanism. The short carrier lifetime and its very weak temperature-dependent behavior suggests that the carrier lifetime is mainly determined by the carrier capture process by defect levels in GaSb.